(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Busulfan is a chemotherapy treatment for cancer patients, and in comparison with the coenzyme ubiquinone is a coenzyme that works to enhance chemical reactions and protect the body from free radicals. It helps in treating cancer and protecting patients undergoing chemotherapy. This study was aimed to investigate the role of ubiquinone against the toxic effect of busulfan on sperm in adult white rats for a period of time, and the experiment was carried out for eight weeks on 24 male adult rats were used, the study was conducted in periods (day 28 ). Distributed in four groups randomly and equally in each group of 6 male rats. The control group injected with distilled water intraperitoneally , second group were injected with busulfan (chemotherapy) only one dose of 10 mg / kg. while animals of third group injected with single dose of busulfan 10 mg / kg plus coenzyme ubiquinone COQ10) 10 mg / kg ) for 4 weeks, while animals in fourth group were injected with the coenzyme ubiquitin coenzyme (COQ10) 10 mg / kg for 4 weeks. At the end of experiment the blood was collected for measuring of blood parameters and hormones levels and sperm analysis has benn done